The contribution of benchmarking to quality improvement in healthcare. A systematic literature review - Claire Willmington; Paolo Belardi; Anna Maria Murante; Milena Vainieri (BMC, 2022)
Abstract Background Benchmarking has been recognised as a valuable method to help identify strengths and weaknesses at all levels of the healthcare system. Despite a growing interest in the practice and study of benchmarking, its contribution to quality of care have not been well elucidated. As such, we conducted a systematic literature review with the aim of synthesizing the evidence regarding the relationship between benchmarking and quality improvement. We also sought to provide evidence on the associated strategies that can be used to further stimulate quality improvement. Methods We searched three databases (PubMed, Web of Science and Scopus) for articles studying the impact of benchmarking on quality of care (processes and outcomes). Following assessment of the articles for inclusion, we conducted data analysis, quality assessment and critical synthesis according to the PRISMA guidelines for systematic literature review. Results A total of 17 articles were identified. All studies reported a positive association between the use of benchmarking and quality improvement in terms of processes (N = 10), outcomes (N = 13) or both (N = 7). In the majority of studies (N = 12), at least one intervention, complementary to benchmarking, was undertaken to stimulate quality improvement. The interventions ranged from meetings between participants to quality improvement plans and financial incentives. A combination of multiple interventions was present in over half of the studies (N = 10). Conclusions The results generated from this review suggest that the practice of benchmarking in healthcare is a growing field, and more research is needed to better understand its effects on quality improvement. Furthermore, our findings indicate that benchmarking may stimulate quality improvement, and that interventions, complementary to benchmarking, seem to reinforce this improvement. Although this study points towards the benefit of combining performance measurement with interventions in terms of quality, future research should further analyse the impact of these interventions individually.